Exploring teachers’ and students’ expectations of good English teachers in Kazakhstan through narrative and metaphor analyses - Zhunussova, Gulnissa (2019)
Significant roles held by a teacher in education have been emphasized for centuries. However, due to the paucity of studies in this area it is not clear what factors contribute to features of a good English teacher as perceived by participants themselves in specific educational settings. The aim of this mixed methods research is to explore university students’ and teachers’ expectations of good English teachers in Kazakhstan: this is arguably the first such examination within a Kazakhstani context. 299 undergraduate students and 43 university English teachers from six cities in Kazakhstan completed a metaphor questionnaire. Subsequently, narrative interviews were conducted with 100 students and 43 teachers. Drawing on this original combination of less conventional research methods, this study provides a framework to examine the scope of conceptions of EFL (English as a Foreign Language) teachers. The uniqueness of this research lies in investigating both teachers’ and students’ views through a combination of narrative and metaphor analyses which provide innovative methods to explore insights on the topic from participants’ perspectives. Overall, the results suggest that teachers’ and students’ expectations of good EFL teachers in Kazakhstan go beyond learners’ academic and linguistic development. Both teachers and students perceive a good EFL teacher within complex relationships of equally important and mutually dependent cognitive, affective, social, moral and aesthetic dimensions of conceptions of a good English teacher. This multidimensional model of an EFL teacher is one of the key aspects within a proposed framework of concepts of EFL teachers. It is argued that cultures of learning in this framework underpin students’ and teachers’ expectations of good EFL teachers and can influence second language teacher education design in Kazakhstan. The inductively derived framework represents an EFL teacher in holistic terms: it portrays a nonconventional landscape with theoretical and practical implications rather than prescribing a fixed set of predetermined characteristics expected from EFL teachers. Such a shift in theory and practice should help gain a better understanding of EFL teachers which is likely to enhance EFL teaching and learning.